When global meets local: Action learning, positionality and postcolonialism. Issue 1 (February 2021) - Mughal, Farooq
This article explores changes in the positionality of Pakistani MBA students as they undergo an action learning (AL) intervention designed to encourage group reflection for the purpose of stimulating self-directed learning. Findings from this article suggest that reflecting openly and challenging deep-seated beliefs in AL groups disrupts learner positionality, creating temporary misalignment with embodied cultural dispositions which shape social interactions and relationships. When applied in the context of Pakistani business schools, public reflection in action learning groups creates dynamics resulting in three broad participant responses that trigger realignment with cultural norms: dissonance, aversion and ambivalence . As facilitators and educators, overlooking such responses to attempt empowering learners and encouraging self-direction can result in the unconscious reinforcement of power relationships that the reflective practice of action learning seeks to challenge.